Critical Analysis of Islamic Education Textbooks and Morals for VII Grade Curriculum 2013 - Imam Taufik; Istikomah Istikomah (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Islamic Education is one of the fields of study that must be provided for elementary to tertiary education under the Ministry of Education and Culture and the Ministry of Religion of the Republic of Indonesia. The learning activities can not be separated from the source of learning, one of which is the textbook of Islamic Education and Morals. This study aims to conduct a critical analysis of the content of the book on Islamic Education and Morals for class VII, which is focused on analyzing the discussion material in the book and the suitability of the content with genuine arguments contained in the Qur'an and Hadith. This research belongs to qualitative research with a library approach in collecting data using documentation techniques and data analysis using content analysis techniques. The results obtained in this study are Islamic Education Textbooks and Morals Class VII Published by the Ministry of Education and Culture of the Republic of Indonesia. There are four types of discussions: Akidah Akhlak, Fiqh, History of Islamic Culture and Al-Qur'an Hadith, and the verses. The material is by the arguments contained in the Qur'an and Hadith so that it is appropriate to be used as a learning resource.